2022
DOI: 10.1080/0960085x.2022.2103045
|View full text |Cite
|
Sign up to set email alerts
|

The impact of enterprise architecture management on information systems architecture complexity

Abstract: Significant investments in information systems (IS) over the past decades have led to increasingly complex IS architectures in organisations, which are difficult to understand, operate, and maintain. We investigate this development and associated challenges through a conceptual model that distinguishes four constituent elements of IS architecture complexity by differentiating technological from organisational aspects and structural from dynamic aspects. Building on this conceptualisation, we hypothesise relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…On the other hand, EAM research is rarely based on theories. Beese et al (2022) revealed the moderating effect of EAM on the relation between organizational and technical complexity. Organizations that use EAM are able to avoid an increase in technological complexity due to increased organizational complexity.…”
Section: Enterprise Architecture Managementmentioning
confidence: 97%
“…On the other hand, EAM research is rarely based on theories. Beese et al (2022) revealed the moderating effect of EAM on the relation between organizational and technical complexity. Organizations that use EAM are able to avoid an increase in technological complexity due to increased organizational complexity.…”
Section: Enterprise Architecture Managementmentioning
confidence: 97%
“…The authors incorporated TOGAF into the institution's operations to ensure a streamlined procedure, addressing issues such as the lack of a specific financial system and the absence of detailed information and functionalities in the staffing system. Another focus of [5] 's research was evaluating EA implementation to support Industry 4.0. Interviews and surveys were used to assess the planning and capabilities of EA in this context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The synthesis of documents and research related to the DCLT process involves: The compositions of distributed enterprise. A distributed enterprise consists of four components: 1) Distributed business [48][49][50][51][52] is the organization's main strategy, which takes into account the goals, vision, mission, and business operations of each campus. It consists of two sub-components: (1.1) strategy and (1.2) business process.…”
Section: The Dclt Processmentioning
confidence: 99%
“…It consists of three sub-components: (2.1) business applications, (2.2) supporting applications, and (2.3) application programming interfaces. 3) Distributed information [57][58][59][60][61] is the management of all data from organizational processes on every campus. It consists of two sub-components: (3.1) relational information and (3.2) non-relational information.…”
Section: The Dclt Processmentioning
confidence: 99%